What can be learned from action learning coaching? Learnings of novice action learners and their coach. (2nd January 2019) - Carter, Angela Danielle
ABSTRACT: Action learning coaching (ALC), a form of action learning that integrates leadership coaching, is suggested as a method and ethos to build future capacity, specifically in novice HRD practitioners. The purpose of this article is to offer an account of learning from the perspectives of novice action learners, who were new to the field of human resource development (HRD) and to the concept of ALC, as well as their similarly noviced coach. Data from budding practitioners and their coach, participants in an action learning action research (ALAR) study, are analyzed to show how they used action and generative learning through ambiguity to apply learning to their new roles. Action learning coaching elevated participants' skills, self-concept, efficaciousness, professionalism, commitment to action, and capacity for learning and growth. Participants changed themselves, their practice, and ultimately the way they approached human resource development as novices.